1993
DOI: 10.1002/crat.2170280104
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Study of Strained CdTe Powders

Abstract: Lattice strains have been produced in cadmium telluride by grinding for different durations. X-ray diffractograms have been obtained at different stages of grinding. The lattice constants, particle size, lattice strain and Debye-Waller factors have been determined. From the correlation between the strain and the effective Debye-Waller factor, the Debye-Waller factor for zero strain has been estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
(2 reference statements)
4
8
0
Order By: Relevance
“…Thus, whenever Debye-Waller factors are determined from X-ray intensities on powder samples, it is desirable, to make an estimate of the lattice strain and if the strain is large, a suitable correction is to be made as in the present study. This is similar to observations of Inagaki et al 20 21 Sirdeshmuch et al 22 Krishna and Sirdeshmukh 23 and Krishna et al 24 In the present work the Debye-Waller factor increases with milling time and lattice strain in a slightly non-linear fashion. Figure 6 shows the variation between the lattice strain ( ) and Debye-Waller factor (B).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, whenever Debye-Waller factors are determined from X-ray intensities on powder samples, it is desirable, to make an estimate of the lattice strain and if the strain is large, a suitable correction is to be made as in the present study. This is similar to observations of Inagaki et al 20 21 Sirdeshmuch et al 22 Krishna and Sirdeshmukh 23 and Krishna et al 24 In the present work the Debye-Waller factor increases with milling time and lattice strain in a slightly non-linear fashion. Figure 6 shows the variation between the lattice strain ( ) and Debye-Waller factor (B).…”
Section: Resultssupporting
confidence: 93%
“…Inagaki et al 20 21 showed that in several non-metallic powders, the strains produced during grinding have a significant effect on the Debye-Waller factors measured from X-ray diffraction intensities. Sirdeshmukh et al 22 observed the effect of lattice strains on the DebyeWaller factors in semiconductor powder materials. Krishna and Sirdeshmukh 23 studied the effect of lattice strains on the Debye-Waller factor of ytterbium metal.…”
Section: Introductionmentioning
confidence: 98%
“…Both lattice strain and Debye-Waller factor increase with grinding time. This is similar to the observations of Inagaki et al [5,6], Sirdeshmukh et al [7] and Gopi Krishna and Sirdeshmukh [8]. In all three cases, the Debye-Waller factor increases with grinding time and lattice strain in a slightly non-linear fashion.…”
supporting
confidence: 89%
“…Inagaki et al [5,6] showed that in several non-metallic powders, the strains produced during grinding have a significant effect on the Debye-Waller factors measured from X-ray diffraction intensities. Sirdeshmukh et al [7] observed the effect of lattice strains on the Debye-Waller factors in semiconductor powder materials. Gopi Krishna and Sirdeshmukh [8] studied the effect of lattice strains on the Debye-Waller factor of ytterbium metal.…”
mentioning
confidence: 98%
“…Thus, the increased in unit cell volume and decreased in density in treated cadmium indicates that tensile stress may be applied through biofield treatment on cadmium powder [24]. Sirdeshmukh et al reported that lattice strain was generated in cadmium-telluride powder after grinding and milling the powder for different durations [25]. Hence, it is assumed that an energy milling might be induced through biofield treatment, which probably provided the high stress and that might be responsible for internal strain in treated cadmium.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%